SYNTHESIS AND STUDY OF ANTITUBERCULAR ACTIVITY OF PLUMBAGIN ANALOGS - NISHI NAYAK,; MEENAKSHI BAJPAI,; BALKISHEN RAZDAN, (International Journal of Pharma and Bio Sciences, 2014)
Tuberculosis has been a serious public health problem for a long time. With the advent of anti-tubercular antibiotics in the late 1940s, the battle against tuberculosis seemed to have been won but the multi-drug resistance; re-infection and latent infection have become the major cause of concern for the treatment of tuberculosis all over the world. In the present study derivatives of Plumbagin, obtained from Plumbago zeylanica (Family-Plumbaginaceae) have been synthesized. Out of the various analogs synthesized, the antitubercular activity of compound 1,2 and 3 was evaluated using standard H37Rv and S,H,R and E sensitive M. tuberculosis strains using LRF assay method. Compound 1 showed strongest activity against both standard H37Rv and S,H,R and E sensitive M. tuberculosis strains as compared to standard Rifampicin. The other compounds are proved to be more active against standard H37Rv and S,H,R and E sensitive M.tuberculosis strain as compared to Rifampicin.